Growth of Cajuput (Melaleuca leucadendron Linn.) and Longkida (Nauclea orientalis Linn.) in Flooded Condition of Acid Mine Water - Miftahul Mawaddah; Irdika Mansur; Lana Saria (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2012)
Coal mining in Indonesia mostly are conducted using open pit mining system. The method causing exposure of mineral sulphide and triggered the production of acid mine drainage (AMD) when oxidized by O2 and met with water. The problem is encountered by most companies engaged in the coal mining, including PT. Mandiri Intiperkasa. An effort for handling the AMD has been done by establishment of settling pond that was planted with tifa grass (Typha angustifolia). The grass has been khown for its ability to neutralize pH and at the same time absorb heavy metals. However, in term of a long term use of the so called wetland area, it is regarded as non-productive approach. Therefore, it need to sought types of commercial trees species that could survive and grow productively in wetland area to treat the AMD. Treatments were asfollows: a. a combinat ion of species of tifa grass and cajuput (Melaleuca leucadendron Linn.); b. tifa and longkida (Nauclea orientalis Linn.), and c. tifa only. Seedlings were observed for four weeks. Variables observed were: diameter growth, high growth, pH of the AMD, the weight of dried plants, the ratio (apa?), the roots and shoot nutrient analyses, and analysis of mud. The increase in the pH of AMD occurs every week on each unit test. Both types either cajuput and longkida able to survive and grow well for four weeks in the wet land flooded with AMD.